(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Diabetes is a disease that can accompany a person throughout his life (congenital form), or take him by surprise at any age (acquired form). But this disease does not become a death sentence, although it causes discomfort to a person, limiting his life and obliging him to lead a certain lifestyle. A person becomes dependent on drugs